Hypoalbuminaemia as a Prognostic Biomarker of First-Line Treatment Resistance in Metastatic Non-small Cell Lung Cancer - Stares, Mark; Swan, Amanda; Cumming, Kirsten; Ding, Tze-En; Leach, James; Stratton, Cory; Thomson, Findlay; Barrie, Colin; MacLennan, Kirsty; Campbell, Sorcha; Evans, Tamasin; Tufail, Aisha; et al. (Frontiers in Nutrition, 2021)
INTRODUCTION Despite significant advances in systemic anticancer therapy (SACT) for non-small cell lung cancer (NSCLC) many patients fail to respond to treatment or develop treatment resistance. Albumin, a biomarker of systemic inflammation and malnutrition, predicts survival in many cancers. We evaluated the prognostic significance of albumin in patients receiving first-line targeted therapy or immunotherapy-based SACT for metastatic NSCLC. METHODS All patients treated with first-line targeted therapy or immunotherapy-based SACT for metastatic NSCLC at a regional Scottish cancer centre were identified. Serum albumin at pre-treatment, after 12-weeks of treatment and at the time of progressive disease were recorded. The relationship between albumin (≥35g/L v <35g/L) and overall survival (OS) was examined. RESULTS Data were available for 389 patients: targeted therapy cohort (n=159) and immunotherapy-based therapy cohort (n=230). Pre-treatment albumin was predictive of OS in each cohort (HR1.82 (95%CI 1.23-2.70) (p=0.003) and HR2.55 (95%CI 1.78-3.65) (p<0.001) respectively. Pre-treatment albumin <35g/L was associated with a significantly higher relative-risk of death within 12 weeks in each cohort (9.58 (95%CI 2.20-41.72, p=0.003) and RR3.60 (95%CI 1.74-6.57, p<0.001) respectively). 12-week albumin was predictive of OS in each cohort (HR2.88 (95%CI 1.86-4.46) (p<0.001) and HR2.67 (95%CI 1.74-4.08) (p<0.001)) respectively). 46/133 (35%) of evaluable patients treated with targeted therapy and 43/169 (25%) crossed over albumin prognostic groups between pre-treatment and 12-week. The prognostic value of 12-week albumin was independent of pre-treatment albumin status. A majority of patients had albumin <35g/L at the time of progressive disease, when it was also predictive of survival following progressive disease (HR2.48 (95%CI 1.61-3.82) (p<0.001) and HR2.87 (95%CI 1.91-4.31) (p<0.001) respectively). CONCLUSIONS Albumin is a reliable prognostic factor in patients with metastatic NSCLC, predicting survival independent of class of drug treatment at various time points during the patient journey. Tracking albumin concentrations during systemic therapy may indicate disease activity or treatment response over time.